Proposal of a mosquito control plan of Smir-Restinga region (north-west of Morocco) - Mariam El Joubari; Anass Louah; Oumnia Himmi (Journal of Basic and Applied Zoology, 2024)
Abstract Background The present study conducted on mosquitoes in the region of Restinga Smir, located in the north-west of Morocco, attempts to provide a scientific platform for an appropriate mosquito control plan for this tourism spot. The aim of this plan is to perfect the methods of the means of mosquito control for an effective fight against mosquitoes in this area, known for their strong nuisance (bites) and their ability to transmit several deadly diseases. Results Monitoring of mosquito species in the Smir marshes, especially those of public health interest, shows that they are distributed differently in the permanent and temporary environments. The establishment and analysis of their development cycles shows that their periods of activity in the different stations of the study area overlap in several cases, especially in the permanent stations. The study of the resistance of these species to the organophosphate insecticides commonly used for mosquito control in the region allowed to conclude the doses of insecticides (LC 90) that could be used for this mosquito control programme. Conclusions The proposed mosquito control programme gives an estimate of the timing of larval treatments and the insecticides that may be used. This plan was concluded based on the results obtained from the study of life cycles, spatial and temporal distribution of mosquitoes in the Smir area and their resistance to the organophosphate insecticides most used by public health services.